2022
DOI: 10.31004/obsesi.v6i6.3558
|View full text |Cite
|
Sign up to set email alerts
|

Peningkatan Perkembangan Kognitif Anak Usia Dini dengan Kebiasaan Menonton Video Kartun Pembelajaran

Abstract: Gadget merupakan salah satu bukti berkembangnya teknologi dan informasi yang sangat pesat. Anak menggunakan gadget untuk menonton video kartun yang dapat memengaruhi perkembangan kognitif anak. Tulisan ini menjelaskan bagaimana kaitan antara kebiasaan menonton vidio kartun pembelajaran dengan perkembangan kognitif anak usia dini di RA Perwanida 01 Pancir Kab. Blitar. Desain penelitian yang digunakan adalah deskriptif korelasi. Pendekatan menggunakan cross sectional dengan uji pearson correlation dan kruskal wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
1
0
0
Order By: Relevance
“…Cognitive development is the most important part of child development because all information is assimilated through cognitive development and this development can be stimulated through interactive video and knowledge video activities (Aulia et al, 2022). The results of the small-scale and large-scale trials also showed a very good percentage level by users, this is in accordance with research previously conducted by (Utami et al, 2021) which states that the use of Qr Code is effectively used to provide material understanding.…”
Section: Discussionsupporting
confidence: 87%
“…Cognitive development is the most important part of child development because all information is assimilated through cognitive development and this development can be stimulated through interactive video and knowledge video activities (Aulia et al, 2022). The results of the small-scale and large-scale trials also showed a very good percentage level by users, this is in accordance with research previously conducted by (Utami et al, 2021) which states that the use of Qr Code is effectively used to provide material understanding.…”
Section: Discussionsupporting
confidence: 87%
“…Guru bekerjasama dengan orang tua anak di kelompok B dengan cara memberikan sebuah video interaktif yang ditayangkan di sekolah kemudian orang tua pada saat dirumah menunjukkan kembali video tersebut kepada anak sambil bercerita dan tanya jawab. Dengan hal ini orang tua mampu untuk berperan memberikan arahan sebagai upaya mencegah akibat negatif dari penggunaan gadget atau smartphone (Aulia et al, 2022). Dalam video yang ditampilkan terdapat beberapa sikap moral yang bisa diterapkan untuk anak diantaranya sikap tanggung jawab, mandiri, percaya diri, dan disiplin.…”
Section: Hasil Dan Pembahasanunclassified